M-Government Application for Retrieving Users Queries Based on WAP Technology in the Rural Communities Area - Basha, Ahmed Dheyaa (2010)
Today's, mobile applications have brought the different advantages for accessing and sharing information over wireless application protocol (WAP). There are difficulties for accessing and searching information especially in the rural communities. Hence, the study aimed to develop a mobile application for accessing and retrieving user queries over WAP technology. Moreover, the proposed application will provide users in rural communities with their request information about different events, such as (News, clinics, stations, and other events). Furthermore, Application Development Modified Methodology (Charles, 1995) has been used for building the proposed application. Finally, the proposed application has been evaluated and the obtained results have been produces.